Generalizing the variational theory on time scales to include the delta indefinite integral - Martins, N.
We prove necessary optimality conditions of EulerLagrange type for generalized problems of the calculus of variations on time scales with a Lagrangian depending not only on the independent variable, an unknown function and its delta derivative, but also on a delta indefinite integral that depends on the unknown function. Such kinds of variational problems were considered by Euler himself and have been recently investigated in [J. Gregory, Generalizing variational theory to include the indefinite integral, higher derivatives, and a variety of means as cost variables, Methods Appl. Anal. 15 (4) (2008) 427435]. Our results not only provide a generalization to previous results, but also give some other interesting optimality conditions as special cases. © 2011 Elsevier Ltd. All rights reserved.